Further Evidence of the Relative Stability Evaluation of Lewis Acid Base Complexes - Humadi, Salah Aldin Jassim; Mohammed, Leqaa Adnan; Hassan, Ekhlas Abdallah (Al-Nahrain Journal of Science, 2018)
Through Lewis acid-base complexation concept, interaction between three types of Lewis acid (BCl3, AlCl3 and SiCl4) as acceptors and many oxygen containing ether groups (such as dimethyl ether, ethyl methyl ether, cyclohexyl methyl ether, phenyl methyl ether, 1,2 dioxane, 1,3 dioxane and 1,4 dioxane) as donor ligands were evaluated based on several parameters including chemical potential, Global softness, HOMO- LUMO shapes and interaction energy of formed complexes.Theoretical computational Density Functional Theory (DFT) and Hatree-Fock (HF) were used in addition to some empirical equations from literature to calculate the above mentioned parameters. This work proved that cyclohexyl methyl ether formed the most stable complex with silicon tetrachloride and the least stable complex being BCl3 bond to dimetyl ether. This work provides further evidence that the relative Lewis acidity depends on the groups attached to the doner atom, and do not depend on the central atom of acid molecule.